USING THINK-AHEAD AND WRITE (TAW) STRATEGY TO IMPROVE STUDENTS' WRITING SKILL IN DESCRIPTIVE TEXT - Evi Safitri Yulandari; Hendra Suryadi (JURNAL ILMIAH GLOBAL EDUCATION, 2022)
According to the school-based curriculum (K-13) there are several types of texts that students study. Descriptive text is one of the texts that must be mastered by students. Descriptive text is a general text that students already know, but most students are still confused when they want to describe something. Writing is an important skill, but in reality there are still many students who have difficulty writing a sentence and making it into a perfect paragraph. This study aims to improve students' writing skills in descriptive texts by using Think-Ahead and Write (TAW) strategies in class XI SMA. The use of Think-Ahead and Write (TAW) strategy is an effort that is needed to improve students' learning abilities, especially to improve students' writing skills. Think-Ahead and Write (TAW) is a strategy that can help students understand the concept of writing to develop students' thinking skills. Using this type of descriptive qualitative research and as a sample the students of class XI SMAN 1 Batukliang were selected. Data collection in this study used the following instruments: observation, interviews and questionnaires to analyze the data in descriptive qualitative form. More specifically, this research is expected to be able to describe (1.) whether the teacher is able to implement or not teach descriptive text writing skills using the TAW strategy; (2) how teachers implement TAW strategies in learning; (3) Students' understanding in producing descriptive text using TAW strategy. This research is planned for 1 year, while the mandatory output target of this research is to publish articles in accredited national journals ranked 1-6. This research is at TKT 2. This research is expected to be a window for further studies or references to explore the potential benefits and challenges of the Think-Ahead And Write (TAW) strategy itself in learning to write descriptive texts, especially for secondary education (SMA).